Evaluating successes and challenges for effective governance of privately protected areas in Australia - Brugler, Sarah (Frontiers in Conservation Science, 2023)
Australia has one of the world's largest privately protected area (PPA) estates and has been seen as a world leader in establishing PPAs, with significant growth since 2000. Despite the policy expectation that PPAs will continue to grow in Australia, there has been limited policy or academic consideration of the legal and governance arrangements that are best placed to enable this. This article uses adaptive governance as a conceptual framework for conducting doctrinal (to explore the legal rules) and socio-legal (to understand the implication and effects of the rules in practice) research to analyze the governance of conservation covenant regimes in Australia, with a particular focus on the State of Victoria. The article finds that Victoria’s conservation covenant regime has the legal foundations to enable adaptive governance and that conservation covenants are expected to continue to be important in maintaining and establishing new PPAs, with opportunities for covenants to similarly deliver ecosystem restoration and climate adaptation objectives. Ongoing adequate public investment in the regime and the ability of the regime to attract new landowners in important landscapes without better financial incentives are identified as key challenges. The analyses and findings, while focused on the Australian context, are expected to have applicability to other jurisdictions that are focused on implementing the Kunming-Montreal Global Biodiversity Framework and policies related to protected areas, private land conservation, ecosystem restoration, and climate adaptation.